Kalaripayatt : the ancient indian art of self defence - Stanis3aw Tokarski (Archives of Budo, 2007; Vol. 3: 15-20, 2007)
This article has not been the result of the strict empirical research. But the point of depart has been of the practical nature. For many years I have been studying the various self-defence systems of Asiatic combat sports and martial arts. As the point of depart I have chosen judo. I have black belt (4th Dan). In 1964 I won the gold in University Championship of Europe. About the same time I have been graduated at Oriental Department of Warsaw University. Than my researches on Asian martial arts have began, for more than two decades I have been interested in the studies of the cultural background of armed and unarmed combat. Some legends situated the cradle of martial arts in Bharatavarsha or in the country of Buddha's birth. Although I have written two books about it, I could not study the ancient Indian systems of self-defence. But in 2005 situation has been changed: I have got a rare opportunity to go to India -to g et some glimpses of the ethos and etnos of various implications of ancient Dhanur Veda. Within the scheme of I.C.C.R. (Indian Council for Cultural Relations) I have travelled all over India. My introductory refl ection on kalari written above aims at the larger interdisciplinary and intercultural project of research on this subject. To launch it at academic level, I look forward for some experienced partners - the experts and scholars